The mystical and the mundane: the human/animal distinction in Animal Parade. Issue 2 (3rd April 2019) - Brisini, Travis
ABSTRACT: This essay is a response to Christopher Collins' "Animal Parade." The author reflects on the productive ambiguity in Collins' representation of non-human animals, and offers preliminary thoughts on the relationship between performance and mysticism in a posthumanist context.